Perancangan Interior NestlÃ©âs Cereal World di Surabaya - Mariana Wibowo, Linda Gunawan (Intra, 2014)
NestlÃ©âs Cereal World is a new facility in foodservice industry, which people can explore and obtain a new experience about cereal through 4 main facilities: attraction, discover, dining, and shopping. NestlÃ©âs Cereal World design will use NestlÃ©âs interior branding, which the tangible and intangible design will represent the NestlÃ©âs Cereal identity.